Security testing for mobile blockchain application - Ang, Keith Kok Jun (Nanyang Technological University, 2020)
In today’s society, the obscure blockchain technology has garnered much attention, having up to a thousand cryptocurrencies. The 51% attack has always been deemed unlikely for a long period of time. However, it still poses a problem to unpopular or newer blockchains implementation. This paper will be on creating an easily reproducible playground for experimenting the 51% attack.